2022
DOI: 10.1097/aco.0000000000001121
|View full text |Cite
|
Sign up to set email alerts
|

Opioid abuse and perioperative care: a new medical disease

Abstract: Purpose of reviewThis review article aims to describe the perioperative clinical implications of opioid use or opioid use disorder (OUD) and to provide recommendations related to analgesia, anesthesia, and postoperative care for patients with this 'new medical disease'. Recent findingsEvidence suggest that 1 in 4 surgical patients will be using opioids preoperatively. Management of these patients, or those with OUD, can be challenging given their opioid tolerance, hyperalgesia, decreased pain tolerance, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…the risk of postoperative pain is increased [18]. The regular use of preoperative painkillers will be an independent risk factor, especially if opioids are used preoperatively [19 ▪ ]. In general, young patients tend to have more pain than elderly [20 ▪ ], and females more than men.…”
Section: Individual Preoperative Risk Of Postoperative Painmentioning
confidence: 99%
See 1 more Smart Citation
“…the risk of postoperative pain is increased [18]. The regular use of preoperative painkillers will be an independent risk factor, especially if opioids are used preoperatively [19 ▪ ]. In general, young patients tend to have more pain than elderly [20 ▪ ], and females more than men.…”
Section: Individual Preoperative Risk Of Postoperative Painmentioning
confidence: 99%
“…[44,45]. However, the have a number of well known side-effects and especially hyperalgesia and the addiction potential are much in focus presently [2,19 ▪ ]. It has been shown that high-dose per-operative opioid may increase the risk of postoperative pain, and opioid-free anaesthesia has been suggested as a measure to reduce postoperative pain.…”
Section: The Opioidsmentioning
confidence: 99%
“…The authors also suggested that the preemptive visceral analgesic effect of pre-incisional TPVB should be studied for surgeries other than LC. Henshaw et al [ 9 ] argued that opioid abuse should be recognized as a new disease and suggested that enhanced postoperative monitoring, multimodal analgesia, and a plan for preoperative opioid management may help modify the risks of adverse postoperative outcomes. Thus, the need for anesthesiologists to join in the efforts to reduce opioid use during the perioperative period and take a lead in discovering new pain management methods is growing.…”
mentioning
confidence: 99%
“…The authors also suggested that the preemptive visceral analgesic effect of pre-incisional TPVB should be studied for surgeries other than LC. Henshaw et al [9] argued that opioid abuse should be recognized as a new disease and suggested that enhanced postoperative monitoring, multimodal analgesia, and a plan for preoperative opi-…”
mentioning
confidence: 99%